LncRNA TUG1 mitigates chronic kidney disease through miR-542-3p/HIF-1α/VEGF axis - Luoxiang Qian; Wanru Hu; Yanping Wang; Yousuf Abdulkarim Waheed; Shuqun Hu; Dong Sun; Shulin Li (Heliyon)
Renal interstitial fibrosis (RIF) is a common pathway in chronic kidney disease (CKD) that ultimately leads to end-stage renal failure, worsening both glomerulosclerosis and interstitial fibrosis. Ten percent of the adult population in the world suffers from CKD, and as the ageing population continues to rise, it is increasingly regarded as a global threat—a silent epidemic. CKD has been discovered to be closely associated with both long noncoding RNAs (lncRNAs) and microRNAs (miRNAs), while the precise molecular processes behind this relationship are still unclear. This study evaluated the impact of miR-542-3p and lncRNA TUG1 on renal fibrosis, along with the underlying regulatory mechanisms. Through in vitro tube formation assays, research demonstrated that knocking down lncRNA TUG1 may enhance angiogenesis and repair damaged endothelial cell-cell connections. We used Western blot and qRT-PCR methods in the unilateral ureteral obstruction (UUO) model to identify tissue hypoxia and fibrotic lesions. Additionally, a cutting-edge method known as fluorescence microangiography (FMA) was employed to detect damage to the peritubular capillaries (PTCs), with MATLAB software utilised for data evaluation. Furthermore, the coexpression of CD31 and α-SMA helped identify cells in the obstructed kidney that were transitioning from endothelium to myofibroblasts. On the contrary, lncRNA TUG1 downregulation showed a protective effect against the transition from endothelial cells to myofibroblasts. Additionally, knocking down lncRNA TUG1 has been shown to reduce the expression of fibrotic markers by alleviating tissue hypoxia. This effect was significantly counteracted by the inhibition of miR-542-3p. Collectively, our findings offer fresh perspectives on how lncRNA TUG1 and the miR-542-3p/HIF-1α/VEGF axis are regulated as renal fibrosis advances.